Learning Organization in Determining Supply Chain Performance - Khairul Ikhwan; Budi Rahardjo; Shinta Ratnawati (School of Business, Bogor Agricultural University (SB-IPB), 2021)
Most learning organization studies have focused on enhancing the organization’s performance. However, learning organization extends beyond knowledge management that makes the organization more adaptable and more responsive to the challenges of a fast-changing business environment. The application of a learning organization is an alternative step for companies to be able to face the challenges of the fast-changing business environment. This paper aims to identify the effect of learning organizations on supply chain performance. This study adds the effect of transformational leadership as a variable that affects the comprehensive understanding of learning organizations to gain a. Structural Equation Modelling – Partial Least Square (SEM-PLS) was used to reveal that learning organization has no significant impact on supply chain performance. However, learning organization affected supply chain driver. The Supply chain driver has a positive and significant impact on supply chain performance. Leadership style has a positive and significant impact on learning organization. Organization can make better decisions on choosing facilities more efficiently, managing supplies efficiently and be can use the information itself to increase profits by implementing learning organization. Keywords: learning organization, SEM-PLS, supply chain performance, leadership, supply chain driver